PENGARUH KEPEMIMPINAN, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KEMENTERIAN AGAMA KANTOR WILAYAH BANTEN - Dade Suparna; Faiz El Jihad (Universitas La Tansa Mashiro, 2020)
The purpose of this study was to determine the effect of leadership, compensation, and work discipline on the performance of the Ministry of Religion Employees of the Banten Provincial office. This study uses a survey method using primary data obtained from questionnaires. The sample in this study was 130 employees. Samples were taken by random sampling technique, which is a random sampling technique. The results showed that: (1) leadership had a significant positive effect on employee performance. (2) compensation has a significant positive effect on employee performance. (3) work discipline has a significant positive effect on the performance of the employees of the Ministry of Religion in the Banten Regional office.